Evaluation of guava cultivars for processing and biochemical changes in nectar beverage during storage (Indian Journal of Arid Horticulture, 2025)
The beverages are becoming more popular in comparison to synthetic or carbonated drinks which are available in the market. In view of this, fruit beverages of guava have a great potential in processing industry due to its excellent flavour and nutritive value. Looking to the demand of natural beverages, the present study was carried out during the year 2003-04. The experimental material consisted of four cultivars of guava and six recipes maintained for making nectar beverage with varying levels of TSS per cent. The prepared nectar was kept under ambient condition for storage study up to 150 days. The beverage prepared from the cultivar L-49 had highest content of ascorbic acid and also scored highest organoleptic value. While, acidity, reducing and total sugar were found to be highest in cultivar R-72. Among various recipes tried in this investigation, the nectar prepared from 20 per cent pulp, 0.3 per cent acidity and 17 per cent TSS recorded highest ascorbic acid and organoleptic value. During storage of nectar, the acidity, reducing sugar and total sugar showed an increasing trend with increasing period of storage (0 to 150 days) under ambient condition. While, there was a decreasing trend of ascorbic acid and organoleptic score during storage period upto 150 days under ambient condition.
Keywords: Ambient condition; biochemical changes; guava cultivars; nectar; recipes and storage